2021
DOI: 10.1186/s12884-021-04214-5
|View full text |Cite
|
Sign up to set email alerts
|

Ralstonia mannitolilytica sepsis after elective cesarean delivery: a case report

Abstract: Background Ralstonia mannitolilytica, a newly emerging opportunistic pathogen worldwide, has been reported to be responsible for human pneumonia, septicemia and meningitis. This is the first report of a case of Ralstonia mannitolilytica sepsis after elective cesarean delivery. Case presentation A 25-year-old woman, gravida 1 para 0, was scheduled for an elective cesarean delivery at 39+ 1 weeks of gestation. Sudden high fever and decreased blood pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…There are few national and international reports, and there are current case reports of cystic fibrosis with infection, elderly hospital-acquired pneumonia, bronchiectasis, chronic obstructive pulmonary disease, bacteremia, solid cancer, abdominal dialysis tube infection, neonatal, hematologic, renal transplantation, diabetes mellitus, scleroderma, meningitis, peritonitis, osteomyelitis, abdominal blood collection infection, and urinary tract infection. Elderly patients, those with multiple underlying diseases, those using broad-spectrum antibacterial drugs, and those receiving invasive mechanical ventilation are at an increased risk of infection with this organism [ 32 , 34 45 ]. Although previous reports showed that the infection caused by R. mannitolilytica is more common in immunocompromised groups, the report of R. mannitolilytica infection in the normal immunity population is rare, and the specific mechanism is still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…There are few national and international reports, and there are current case reports of cystic fibrosis with infection, elderly hospital-acquired pneumonia, bronchiectasis, chronic obstructive pulmonary disease, bacteremia, solid cancer, abdominal dialysis tube infection, neonatal, hematologic, renal transplantation, diabetes mellitus, scleroderma, meningitis, peritonitis, osteomyelitis, abdominal blood collection infection, and urinary tract infection. Elderly patients, those with multiple underlying diseases, those using broad-spectrum antibacterial drugs, and those receiving invasive mechanical ventilation are at an increased risk of infection with this organism [ 32 , 34 45 ]. Although previous reports showed that the infection caused by R. mannitolilytica is more common in immunocompromised groups, the report of R. mannitolilytica infection in the normal immunity population is rare, and the specific mechanism is still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…R. mannitolilytica are known to cause sepsis, meningitis and central venous catheterassociated bacteraemia [3]. Of late several case reports of infections by R. mannitolilytica have been seen from India and worldwide [4][5][6][7][8][9][10][11][12]. Many case reports have highlighted R. mannitolilytica as causing bacteraemia and sepsis [4][5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Of late several case reports of infections by R. mannitolilytica have been seen from India and worldwide [4][5][6][7][8][9][10][11][12]. Many case reports have highlighted R. mannitolilytica as causing bacteraemia and sepsis [4][5][6][7][8][9][10][11]. Lampropoulos et al (2021) and Rajendran et al (2022) highlighted the organism as an emerging opportunistic pathogen causing sepsis in neonatal intensive care units [9,10] .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations